Mini Review of Biochemical Basis, Diagnosis and Management of Crush Syndrome - Hamlah, Abdulhalim; Tarabishy, Abd Alraouf; Al-Madhagi, Haitham (Acta medica Lituanica, 2023)
Crush syndrome (CS) is a metabolic disorder whose victims are individuals suffered from natural disasters such as earthquake or man-made conflicts. CS complications include acute kidney injury and cardiac arrhythmia that collectively end with death if untreated immediately. These complications are accounted for the liberation of damaged muscle tissues contents, primarily myoglobin and potassium. The present mini review discusses the biochemical basis of the development of CS. In addition, diagnosis and management and the application of novel experimental therapeutics of CS are also highlighted.